A synoptic framework and future directions for placental pathology reporting. (February 2019) - Benton, Samantha J.; Lafreniere, Anthea J.; Grynspan, David; Bainbridge, Shannon A.
Abstract: Placental pathology is a key modality for determining placental health during pregnancy, especially in the event of adverse pregnancy outcomes. However, issues with standardization in placental diagnosis, reporting practices and clinical translation prevent this modality from being used to its full potential. This article will highlight these standardization issues and summarize ongoing work in this field to overcome them. Additionally, we propose a synoptic reporting framework for placental pathology based on current consensus guidelines, aimed at enhancing the comprehensiveness and quality of reporting placental findings. We believe this approach will improve our understanding of the placenta in adverse pregnancy outcomes and, importantly, offer the opportunity to increase knowledge translation to key stakeholder groups including patients. Highlights: Placental pathology is hindered by lack of standardization in reporting practices. Presented is a synoptic reporting framework founded on current consensus guidelines. The synoptic framework has broad applicability to clinical and research applications. Individualized data abstraction could generate tailored report outputs.